2020
DOI: 10.2147/jpr.s248600
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ultrasound-Guided Corticosteroid Injection in Carpal Tunnel Syndrome: Comparison Between Radial and Ulnar Approaches</p>

Abstract: Purpose: To compare two common approaches for ultrasonography (US)-guided injection. Patients and Methods: Sixty patients with mild-to-moderate CTS were included in this double-blind randomized controlled trial (RCT). They received a single shot of corticosteroid injection through either the US-guided in-plane approach: radial or ulnar side. Participants were evaluated using Boston Carpal Tunnel Questionnaire (BCTQ) and visual analogue scale (VAS) for pain, as well as electrodiagnosis (EDX) and US parameters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…One of the reliable and objective methods for assessing CTS is electrodiagnosis, which reflects the neurophysiological functional status and is useful for grading severity 3 , 4 . Ultrasonography (US) is also widely used because it can quantitatively evaluate swelling of the median nerve and carpal tunnel outlet, and it allows guided administration of the injection through real-time visualization 5 7 . Electrodiagnosis, however, can mainly detect pathologies in thick-myelinated fibers; its sensitivity for detecting injuries of thin-unmyelinated fiber is relatively low 8 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the reliable and objective methods for assessing CTS is electrodiagnosis, which reflects the neurophysiological functional status and is useful for grading severity 3 , 4 . Ultrasonography (US) is also widely used because it can quantitatively evaluate swelling of the median nerve and carpal tunnel outlet, and it allows guided administration of the injection through real-time visualization 5 7 . Electrodiagnosis, however, can mainly detect pathologies in thick-myelinated fibers; its sensitivity for detecting injuries of thin-unmyelinated fiber is relatively low 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Three approaches to carpal tunnel injections can be found in the literature and all of them are performed with a linear transducer of varying frequencies (5-17 MHz). 11,13,14,[26][27][28][29]…”
Section: Approachesmentioning
confidence: 99%
“…Another study with moderate RoB reported less longterm pain, better function and less swelling of the median nerve after injection of the carpal tunnel from the radial rather than from the ulnar site of the wrist. 78 Furthermore, one retrospective cohort study (high RoB) assessed whether there were differences in safety or efficacy outcomes when the needle was placed in the intraepineurium as compared with the extraepineurium, when performing US-guided hydrodissection and GC injection of the median nerve in CTS. 73 The results for safety and clinical efficacy outcomes like function and symptom severity were comparable between groups, while patients receiving intraepineural injections yielded a higher reduction of perinerve oedema 2 weeks after the intervention as compared with those who underwent extraepineural interventions.…”
Section: Kneementioning
confidence: 99%